A312 POST MARKET USE OF TEDUGLUTIDE IN CANADA IN PATIENTS WITH SHORT BOWEL SYNDROME ON HOME PARENTERAL NUTRITION: THE REAL WORLD SETTING. (1st March 2018) - Noelting, J; Jurewitsch, B; Gramlich, L; Duerksen, D; Raman, M; Armstrong, D; Ponta, M L; Saqui, O; Arca-Juico, C K; Kim, P; Stewart, B; Allard, J
Abstract: Background: Patients with intestinal failure due to short bowel syndrome (SBS) are dependent on parenteral support (PS). Teduglutide, a glucagon-like peptide-2 (GLP-2) agonist, can reduce PS requirement by enhancing absorptive capacity of the remaining intestine. As it was only approved for use in Canada in October 2015 and it is indicated for a very select group of patients, not much is known on real-world experience using this drug in Canada. Aims: The aim of this study was to describe the current experience in Canada in using teduglutide. Methods: Data was obtained: 1) from a brief survey on the use of teduglutide, distributed to the HPN programs participating in the Canadian HPN Registry and; 2) from the home parenteral nutrition (HPN) registry itself, where patient data are entered prospectively by HPN teams across Canada. If teduglutide was initiated prior to the patient's baseline entry in the Registry, data was also collected retrospectively. Results: Fifty two patients from 5 provinces were referred by their respective HPN programs for funding of teduglutide. Of these, 21 patients are currently on the drug while 4 had the drug discontinued and 11 were not eligible due to lack of funding. The remaining patients are being assessed or awaiting initiation of the drug. Of those on teduglutide, 18 patients (7 male, 11 female) were entered in the HPN Registry, and, of those who discontinued, 2 (1 male, 1 female) were also entered in the Registry (total: 20). Patients in the Registry are between 26 and 70 years old (mean age 51), with 20cm to 225cm of small bowel and have been on PS from 1 to 29 years (median 5) prior to initiation of the drug. Since initiation of tedulgutide, six patients have discontinued HPN, although 4 of them still receive IV hydration. Of those on teduglutide for 6 and 12 months, PS was reduced by an average of 29% and 43% based on volume and 32% and 34% based on calories, respectively. Fifty-three percent and 82% of patients were able to reduce PS volume by at least 20% after 6 and 12 months of therapy with teduglutide, respectively. The drug was discontinued in two participants due to increased fistula output in one person with uncontrolled Crohn's disease and increased carcinoembryonic antigen in the other. Conclusions: In patients with intestinal failure due to SBS, teduglutide therapy results in reduced dependence on PS. Given the long term complications associated with PS and the limitations of alternative therapies such as intestinal transplantation, teduglutide is a promising new treatment that has the potential to improve the prognosis of this condition. Further, long term studies are needed to determine the sustainability of this therapy and its side effects. Funding Agencies: Ontario Medical Supply, Baxter